P206 Model-predicted lymphocyte response and recovery profiles for the sphingosine 1-phosphate receptor modulators ozanimod and etrasimod. (19th June 2022) - Taylor, Carly; Waterhouse, Timothy; Heathman, Michael; Alex Oh, D; Kiyomi Komori, H; Grundy, John S
Abstract : Introduction: Sphingosine 1-phosphate receptor (S1PR) modulators inhibit lymphocyte egress from lymph nodes, reducing peripheral circulating lymphocyte numbers and their recruitment to inflammation sites. Ozanimod (OZA) is an S1PR modulator approved for multiple sclerosis and ulcerative colitis (UC). The prolonged lymphocyte response following OZA treatment is mainly driven by the long pharmacokinetic (PK) half-life (~11 days) of its active metabolite (CC112273). Etrasimod (ETR (half-life ~33 hours) is an S1PR modulator in clinical development for immune-mediated inflammatory disorders. Exposure-response models describing observed/published PK and pharmacodynamic (PD) data can facilitate comparisons between compounds. Here we present model-predicted lymphocyte response profiles for once-daily dosing of OZA and ETR, and lymphocyte recovery profiles following drug discontinuation. Methods: A population PK/PD model of lymphocyte response to OZA over time was developed from published summary-level data for CC112273 PK profile and an OZA lymphocyte Emax model. Initial model simulation predicted a mean baseline lymphocyte count of 1.97x10 9 /L (slightly higher than observed in the OZA RADIANCE study [1.83x10 9 /L]); thus, a correction factor of 0.93 was applied to subsequent OZA simulations. A population PK/PD model of lymphocyte response to ETR over time was developed using data from 7 Phase 1 studies in healthy volunteers and 2 Phase 2 studies in participants with UC or atopic dermatitis. Simulations from both models of 10, 000 virtual participants given OZA (initial 7-day titration: 0.23mg on Days 1–4, 0.46mg on Days 5–7, 0.92mg on Day 8 and thereafter for 11 weeks) or ETR (2mg for 12 weeks) were produced and compared. Results: Model-predicted lymphocyte response over time approximately (≥90%) reached median steady-state lymphocyte nadir within 24 days for OZA vs within 5 days for ETR ( Figure 1A/1B ). After drug discontinuation, predicted time for lymphocyte counts to return to the lower end of normal (either 0.8x10 9 /L or 1.0x10 9 /L for 90% of virtual participants) was 48 and 81 days, respectively, for OZA and 2 and 4 days, respectively, for ETR. Model predicted results for OZA appear generally consistent with observed lymphocyte findings in its label. Conclusions: Model predictions of lymphocyte response and recovery profiles indicate ETR is expected to achieve lymphocyte nadir faster and require less time to recover to the normal range after discontinuation compared to OZA. Rapid drug washout and immune system reconstitution may be desirable when considering resolution of infection, therapy switches, and family planning.